“Coal Age Galapagos”: Joggins and the Lions of Nineteenth Century Geology - Calder, John (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2006)
ABSTRACT The celebrated coastal section at Joggins, Nova Scotia, has played a seminal role in the development of the Earth Sciences, ﬁguring in the careers of such lions of Nineteenth Century science as Lyell, Dawson, Darwin, Logan, Marsh, Gesner, Agassiz, Wyman and Owen, among others. The story that unfolds is not only one of scientiﬁc discovery, but one of enlightening interactions between the players that brings to life these personalities, their debates and, for some, their personal agendas. The “marvellous chapter of the big volume” of Earth’s history recorded in the sea cliffs at Joggins served as a “Coal Age Galapagos” for Lyell, Darwin, Dawson and others, furthering their case for geological and evolutionary principles that continue to inform scientiﬁc and popular views today. Coincidental with Lyell’s appearance on the scene, Logan undertook at Joggins one of the ﬁrst ﬁeld projects of the Geological Survey of Canada. Against the backdrop of advancing scientiﬁc thought and positions, a penny opera of professional one-upmanship was played out. Gesner sought reprimand of Lyell from Murchison, President of the Geological Society for misleading Nova Scotia’s geologists; Owen, who earlier coined the word “dinosaur”, beat Lyell and Dawson in naming their own discovery; while a young O.C. Marsh, presaging his intensely competitive dinosaur battles with Edward Cope, arrived at Joggins from Yale hot on Lyell and Dawson’s trail, only to be duped by a worldly traveller ready to oblige his desire for fame. Above all others, the work of Dawson in describing the fossil record and its ecological context established a lasting legacy of relevance for the Joggins cliffs.